Actin alpha cardiac muscle 1 gene expression is upregulated in the skeletal muscle of men undergoing androgen deprivation therapy for prostate cancer. Issue 174 (November 2017) - Cheung, Ada S.; de Rooy, Casey; Levinger, Itamar; Rana, Kesha; Clarke, Michele V.; How, Jackie M.; Garnham, Andrew; McLean, Catriona; Zajac, Jeffrey D.; Davey, Rachel A.; Grossmann, Mathis
Highlights: The ACTC1 gene which regulates the fetal form of actin is upregulated in men on ADT. ACTC1 has been associated with improved muscle function in congenital myopathies. ACTC1 may be an initial compensatory response to ADT-induced muscle loss. Abstract: Androgen deprivation therapy (ADT) decreases muscle mass and function but no human studies have investigated the underlying genetic or cellular effects. We tested the hypothesis that ADT will lead to changes in skeletal muscle gene expression, which may explain the adverse muscle phenotype seen clinically. We conducted a prospective cohort study of 9 men with localised prostate cancer who underwent a vastus lateralis biopsy before and after 4 weeks of ADT. Next-generation RNA sequencing was performed and genes differentially expressed following ADT underwent gene ontology mining using Ingenuity Pathway Analysis. Differential expression of genes of interest was confirmed by quantitative PCR (Q-PCR) on gastrocnemius muscle of orchidectomised mice and sham controls (n = 11/group). We found that in men, circulating total testosterone decreased from 16.5 ± 4.3 nmol/L at baseline to 0.4 ± 0.15 nmol/L post-ADT (p < 0.001). RNA sequencing identified 19 differentially expressed genes post-ADT (all p < 0.05 after adjusting for multiple testing). Gene ontology mining identified 8 genes to be of particular interest due to known roles in androgen-mediated signalling; ABCG1, ACTC1, ANKRD1, DMPK, THY1, DCLK1, CST3 were upregulated and SLC38A3 was downregulated post-ADT. Q-PCR in mouse gastrocnemius muscle confirmed that only one gene, Actc1 was concordantly upregulated (p < 0.01) in orchidectomised mice compared with controls. In conclusion, given that ACTC1 upregulation is associated with improved muscle function in certain myopathies, we hypothesise that upregulation of ACTC1 may represent a compensatory response to ADT-induced muscle loss. Further studies will be required to evaluate the role and function of ACTC1 .